Overexpression of cell-cycle related and expression-elevated protein in tumor (CREPT) in malignant cervical cancer. Issue 1 (January 2020) - Wen, Na; Bian, Lihua; Gong, Jing; Meng, Yuanguang
Objective: To explore the expression of cell-cycle related and expression-elevated protein in tumor (CREPT), cyclin D1, and transcription factor 4 (TCF4) in patients with cervical carcinoma. Methods: This study enrolled 20 patients with cervical cancer and 10 control patients diagnosed with benign cervical lesions undergoing resection at the People's Liberation Army General Hospital from January 2016 to December 2017. Cervical tissues were collected from all patients and their clinical characteristics were recorded. Protein and mRNA levels of CREPT, cyclin D1, and TCF4 were measured in tissue samples by immunohistochemistry, western blotting, and real-time polymerase chain reaction (PCR) and compared between the two groups. Result: Protein and mRNA expression levels of CREPT, cyclin D1, and TCF4 were all significantly higher in the cervical cancer compared with the control group, according to western blot and PCR, respectively. CREPT expression was also significantly higher in the cervical cancer group according to immunohistochemistry. Conclusion: Levels of CREPT, cyclin D1, and TCF4 were significantly elevated in cervical carcinoma tissues, and their expression levels were positively correlated, suggesting that these factors might play important roles during the development of cervical carcinoma.